The Influence of Cognitive Therapy on Increasing Self-Esteem in Patients of Low Self-Esteem Due to Schizophrenia at Phala Martha Center, Sukabumi 2022 - Nining Sugihartati; Ratna Fithriyah Sholihany; Nia Kurnia Al-Asyiah; An'nisaa Heriyanti (PT FORMOSA CENDEKIA GLOBAL, 2023)
Individuals who have prolonged feelings of worthlessness, insignificance, and low self-esteem due to negative evaluations of themselves and their abilities are a picture of someone who has low self-esteem (Pardede & Laia, 2020). If the problem of low self-esteem is not dealt with immediately, the client will be insecure and have negative thoughts of himself and others. As a result, the client will tend to be alone and isolate himself from the environment and activities that decrease low self-esteem and can be at risk of social isolation: withdrawing self. Withdrawal is a severe personality disorder in that maladaptive behavior interferes with one's functioning in social relationships. This needs serious attention and handling. This study aimed to determine the effect of cognitive therapy on increasing self-esteem in schizophrenic patients at the Phalamartha Sukabumi Center